2005
DOI: 10.1309/1vfj1c3lp52a4fp8
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Medullary Carcinoma of the Colon

Abstract: We studied 68 sporadic colorectal carcinomas (CRCs) with medullary features (MCRCs) and compared them with 35 poorly differentiated purely "enteric" CRCs (ECRCs) and 15 purely neuroendocrine carcinomas (NECs) of grades II and III, all in patients lacking a family history of CRC. Potential clinicopathologic differences between the study groups were assessed. MCRCs were significantly more common in the ascending colon than were ECRCs, but there was no significant dissimilarity to NECs. ECRCs occurred more often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 38 publications
(47 reference statements)
4
30
1
1
Order By: Relevance
“…She either had hypopituitarism as a consequence of IVL or endocrine dysfunction as a consequence of critical illness. IVL associated with endocrine dysfunction has been described in less than 30 patients [3,4,8,13]. Few reports have been focused on pituitary gland involvement in IVL with consecutive hypopituitarism [8,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…She either had hypopituitarism as a consequence of IVL or endocrine dysfunction as a consequence of critical illness. IVL associated with endocrine dysfunction has been described in less than 30 patients [3,4,8,13]. Few reports have been focused on pituitary gland involvement in IVL with consecutive hypopituitarism [8,13].…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular large B-cell lymphoma (IVL) is a rare generally fatal disease characterized by massive proliferation of lymphoid cells within the small and medium blood vessels, with little or no adjacent parenchymal involvement [1][2][3]. This disorder was previously known as ''malignant angioendotheliomatosis'' or ''angiotropic large-cell lymphoma''.…”
Section: Introductionmentioning
confidence: 99%
“…In both clinical and research settings, medullary carcinoma (MC) is commonly perceived as a distinct clinico-pathological entity with specific prognostic relevance and molecular pathogenesis. A number of studies have suggested that tumors with medullary histology tend to have a favorable clinical outcome and are strongly associated with DNA mismatch repair (MMR) deficiency despite their “poorly differentiated” histologic appearance [3, 4, 6, 810]. As such, the most recent World Health Organization (WHO) classification [11] as well as the American Joint Committee on Cancer (AJCC) [12] have incorporated MC as a distinct histologic subtype.…”
Section: Introductionmentioning
confidence: 99%
“…The number of specific features required for the diagnosis is also widely inconsistent across different studies [3, 6, 8, 9]. MMR deficiency is a stringent diagnostic requirement in some studies [4, 14], but not in others [9, 10]. At present, the only standard diagnostic guideline is that delineated in the 2010 WHO Classification of Tumours of the Digestive System [11], which states concisely that MC is composed of “sheets of malignant cells with vesicular nuclei, prominent nucleoli and abundant eosinophilic cytoplasm, and prominent infiltration by intraepithelial lymphocytes”.…”
Section: Introductionmentioning
confidence: 99%
“…Medullary carcinomas arise frequently in the proximal colon, with an incidence increasing with age and a female predominance 22,23…”
Section: Histopathological Variants Of Colorectal Cancermentioning
confidence: 99%